Can the computer replace the adult for storybook reading? A meta-analysis on the effects of multimedia stories as compared to sharing print stories with an adult - Takacs, Zsofia K.; Swart, Elise K.; Bus, Adriana G. (Frontiers in Psychology, 2014)
The present meta-analysis challenges the notion that young children necessarily need adult scaffolding in order to understand a narrative story and learn words as long as they encounter optimally designed multimedia stories. Including 29 studies and 1272 children, multimedia stories were found more beneficial than encounters with traditional story materials that did not include the help of an adult for story comprehension (g+ = 0.40, k = 18) as well as vocabulary (g+ = 0.30, k = 11). However, no significant differences were found between the learning outcomes of multimedia stories and sharing traditional print-like stories with an adult. It is concluded that multimedia features like animated illustrations, background music and sound effects provide similar scaffolding of story comprehension and word learning as an adult.